Detection of Vibrio Cholerae and Vibrio parahaemolyticus in seafood using MPN-PCR based technique, and their molecular characteristics - Letchumanan, Vengadesh (2013)
Seafood is professed by consumers worldwide to be healthy and nutritious food due to abundance of scientific and documented health benefits. Approximately 90% of global aquaculture production is based in Asia. Nevertheless, recent food borne outbreaks are closely associated with seafood consumption. Seafood is known as a vehicle of transmission of food borne bacteria and causes human illness worldwide. In Malaysia, statistics in year 2009 have shown among the food and water borne diseases, food poisoning has the highest incidence rate of 36.17 per 100,000 populations and with a mortality rate of 0.01 per 100,000 populations. The purpose of this study is to apply and enumerate Vibrio cholerae and Vibrio parahaemolyticus from seafood samples by utilizing the Most Probable Number Method (MPN) and several molecular typing methods including polymerase chain reaction (PCR), enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) and plasmid profiling. The application of conventional method using the Most Probable Number (MPN) method with selective enrichment broth and agar medium is very useful in isolating Vibrio cholerae and Vibrio parahaemolyticus. This method is coupled with PCR based method to obtain specific, sensitive and precise results. The densities enumerated by the MPN-Real Time PCR targeting epsM gene and the MPN-PCR targeting toxR gene is higher than those by MPN-Plate. Genomic DNA of 104 Vibrio cholerae isolates was confirmed by a specific optimized multiplex PCR program targeting hem gene, hlyA gene, ctx gene and zot gene. 10 isolates were tested positive for cholera toxin gene (ctx) gene. All the isolates were positive to hem gene at 519bp and hlyA gene at 738bp but none was tested positive for zot gene. On the other hand, all the 100 Vibrio parahaemolyticus isolates were tested positive for regulatory gene, toxR yielded 368bp. The PCR amplification of the respective genes is a rapid and reliable method of detecting Vibrio cholerae and Vibrio parahaemolyticus isolates from seafood samples. ERIC sequences are short, highly conserved 126 bp non-coding regions found in the Enterobacteriaceae. Its location in bacterial genomes allows discrimination at the genus, species and serovars levels. Dendrogram of ERIC-PCR were analyzed using the Bionumerics Version 6.0 (Applied Maths, Germany) software. From 104 isolates of Vibrio cholerae, ERIC-PCR with primers ERIC-1 and ERIC-2 produced 15 clusters and 9 single isolates at 40% similarity. Where else, 100 isolates of Vibrio parahaemolyticus produced 15 clusters and 6 single isolates at 40% similarity. The results demonstrated that ERIC-PCR is a excellent tool for differentiation and characterization of Vibrio species. Plasmids of Vibrio cholerae and Vibrio parahaemolyticus vary in size from 2.2 Kb to more than 7.4 Kb. Despite limited knowledge on their function, their presence is frequently used for strain differentiation in epidemiological studies. Plasmid profiling of 104 Vibrio cholerae isolates clustered into 19 groups based on the number and pattern of the bands. Where else, plasmid profiling of 100 Vibrio parahaemolyticus isolates clustered into 11 groups based on the number and pattern of the bands. As a conclusion, the concern about possible health illness from Vibrio species, especially when seafood remains as a vehicle of transmission of Vibrio, will continue into the likely future. Therefore, to establish effective control measures to reduce the risk of this bacterium infection and to ensure the safety of foods, surveillance and epidemiology, the employment of molecular methods for the detection of Vibrio cholerae and Vibrio parahaemolyticus in food and environment is important. The results from this study could serve as vital information in Vibrio spp. epidemiology, surveillance, better infection control measures and support of public health policy.